Polyurethane foam composite polyurethane aerogel with high flame retardant property as well as preparation method and application of polyurethane foam composite polyurethane aerogel

By combining the semi-interpenetrating network structure of polyurethane foam and polyurethane aerogel, the problem of insufficient flame retardant performance and mechanical properties in the prior art is solved, and a polyurethane foam/polyurethane composite aerogel with high flame retardant and high mechanical properties is prepared, which is suitable for fire-retardant separation materials and flame-retardant insulation materials of electric vehicle battery packs.

CN120329609APending Publication Date: 2025-07-18NEW MATERIAL INST OF SHANDONG ACADEMY OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510635794.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-16
Publication Date
2025-07-18

AI Technical Summary

Technical Problem

In the prior art, the composite materials of polyurethane aerogel and polyurethane foam have shortcomings in flame retardant properties and mechanical properties, and the preparation process is complex and costly, making it difficult to maintain stability in a long-term working environment.

Method used

By combining the flame retardant with polyurethane foam and polyurethane aerogel in semi-interpenetrating network structure, a simple preparation method including isocyanate dissolution, polyol mixing, catalyst reaction, vacuum impregnation and solvent replacement was used to prepare a polyurethane foam/polyurethane composite aerogel with high flame retardancy and high mechanical properties.

Benefits of technology

The flame retardant and mechanical properties of composite materials have been significantly improved, with an oxygen index of 25%-29%, a tensile strength of 0.8-2.78MPa, a shrinkage of 7.8-11.1%, and a porosity of 75-85%. It is suitable for long-term use in high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120329609A_ABST
    Figure CN120329609A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of organic materials, in particular to a preparation method of polyurethane foam / polyurethane composite aerogel with high flame retardance and high strength. The preparation method comprises the following steps: taking flame-retardant polyurethane aerogel as a filler, fully mixing the flame-retardant polyurethane aerogel with polyurethane foam, then carrying out solvent replacement on the composite wet gel to obtain polyurethane foam / polyurethane composite wet gel, and finally, carrying out normal-pressure drying to obtain the polyurethane foam / polyurethane composite aerogel with high flame retardance and good mechanical properties. The preparation method is simple and efficient, and has a large-scale industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of organic material preparation, and particularly relates to a polyurethane foam composite polyurethane aerogel with high flame retardancy, and a preparation method and application thereof. Background Art

[0002] Polyurethane (PU), whose full name is polycarbamate, is a polymer material formed by the polycondensation reaction of polyols and polyisocyanates and has excellent mechanical properties. It has extremely strong plasticity, but its high flammability limits its sole application; aerogel is an ultra-light material with high porosity and high surface area. Most aerogels are silica-based, and also include carbon and aluminum aerogels; due to its low density and very fragility, it is restricted in thermal insulation applications. Some researchers have added aerogels to polymer foam materials to form composite materials with excellent thermal insulation properties. Liu Qiang et al. studied the synthesis of SiO2 aerogel / polyurethane rigid foam composites in "Research and Characterization of the Influence of Aerogel on the Properties of Polyurethane Rigid Foams", and its mechanical strength needs to be further improved. In the prior art, some researchers have tried to compound the two to balance the performance.

[0003] In the prior art, the flame retardancy of PU aerogel is improved by adding cellulose aerogel or curing agent. For example, the Chinese invention patent with the publication number CN 115651260 A relates to the compounding between polyurethane aerogel and cellulose aerogel. By dispersing inorganic refractory nanomaterials in the polyurethane aerogel, the flame retardant performance of the cellulose / polyurethane aerogel composite material can be imparted. However, the preparation process involves steps such as directional freezing, ball milling and exfoliating nanosheets, multi-step solution mixing and vacuum impregnation. The operating conditions (such as temperature, time, solution ratio) need to be strictly controlled, which increases the production difficulty and cost. Moreover, the second type of aerogel is formed in the porous structure of the first type of aerogel, and it may not be effectively compounded with the polyurethane aerogel inside the cellulose aerogel structure. Although the publication number CN 114539507A proposes a flame retardant polyurethane aerogel and its preparation method, the flame retardant polyurethane aerogel has a small density, good mechanical properties and excellent flame retardant performance. However, it uses a variety of dispersants (such as ACUSOL 445N, KYC-913, etc.), inorganic fillers (fly ash, water glass, hollow glass microspheres, etc.) and modifiers (such as isocyanate, acrylic monomer), which may affect the product performance consistency. Moreover, only the short-term flame retardancy (oxygen index, vertical burning) is tested, but the flame retardancy (oxygen index, vertical burning) of the material under long-term working conditions or the change of mechanical properties after high-temperature aging is not evaluated. Summary of the Invention

[0004] To solve the above technical problems, the object of the present invention is to propose a preparation method and application of polyurethane foam composite polyurethane aerogel with high flame retardancy performance. Through a simple and efficient preparation method, the flame retardancy performance of PU aerogel and PU foam is improved, and a polyurethane foam / polyurethane composite aerogel with both high strength and high porosity is prepared.

[0005] To achieve the above technical object, the present invention adopts the following technical solutions:

[0006] In the first aspect, the present invention provides a preparation method of polyurethane foam composite polyurethane aerogel with high flame retardancy performance, including the following steps:

[0007] S1: Dissolve isocyanate in an organic solvent, and then stir to obtain a prepolymer solution;

[0008] S2: Dissolve polyol in an organic solvent, and then add the prepolymer solution of S1, and stir to form a precursor solution;

[0009] S3: Mix the flame retardant with the precursor solution prepared in S2 to form a mixed solution;

[0010] S4: Add a catalyst to the mixed solution prepared in S3 for reaction, and after crosslinking, a polyurethane wet gel is obtained;

[0011] S5: Use a vacuum oven for vacuum-assisted impregnation for ten minutes, and fully immerse the polyurethane foam into the polyurethane wet gel prepared in S4 to obtain a polyurethane foam / polyurethane wet gel;

[0012] S6: Perform solvent replacement on the polyurethane foam / polyurethane wet gel prepared in S5;

[0013] S7: Perform atmospheric drying on the polyurethane foam / polyurethane wet gel after solvent replacement in S6, and the polyurethane foam composite polyurethane aerogel is obtained.

[0014] In some other embodiments, in step S1, the organic solvent is acetonitrile;

[0015] The isocyanate is hexamethylene diisocyanate;

[0016] In some other embodiments, in step S1, the volume ratio of the amounts of the organic solvent and isocyanate used is (1 - 20) mL : (8 - 17) mL.

[0017] In some other embodiments, in step S2, the polyol is one or more of triethylene glycol, castor oil polyol or polycaprolactone polyol; preferably triethylene glycol.

[0018] In other embodiments of the present invention, the material synthesized from castor oil polyol has poorer flame retardancy than triethylene glycol, and slightly lower compressive strength. Moreover, the ester bond of castor oil is prone to hydrolysis, and long-term use in a humid environment may lead to performance degradation. The glass transition temperature is relatively low, and it is prone to softening at high temperatures (>150°C).

[0019] In other embodiments of the present invention, the material synthesized from polycaprolactone polyol has poorer flame retardancy than triethylene glycol, and additional modification is required; the raw material cost is higher than that of polyether polyol; the upper limit of thermal stability is relatively low (the long-term use temperature is generally <120°C).

[0020] By comparison, it is found that the polyurethane foam synthesized from triethylene glycol is outstanding in terms of flame retardancy, processing efficiency, and high-temperature tolerance, and is particularly suitable for industrial scenarios that require rapid construction, high rigidity, and long-term stability.

[0021] The organic solvent is acetonitrile;

[0022] Preferably, the volume ratio of the organic solvent to the polyol is (1 - 20) mL : (2.67 - 6.23) mL.

[0023] In some other embodiments, in step S3, the flame retardant is tris(1-chloro-2-propyl) phosphate (TCPP) or ammonium polyphosphate;

[0024] The volume ratio of the precursor to the flame retardant is (10 - 25) mL : (0.5 - 3) mL. The precursor is the total amount of the solute polycyanate and polyol in steps S1 and S2.

[0025] In some other embodiments, in step S4, the volume ratio of the precursor to the catalyst is (10 - 25) mL : (0.01 - 0.1) mL.

[0026] The catalyst is dibutyltin dilaurate;

[0027] In one or more embodiments of the present invention, by comparison, it is found that:

[0028] Amine catalysts, such as triethylamine and dimethylamine, have poor selectivity. In addition to catalyzing the reaction between isocyanate and polyol, they also catalyze the reaction between isocyanate and water, resulting in more side reactions and affecting the final performance of the product.

[0029] Acidic catalysts, such as sulfuric acid and phosphoric acid, are corrosive. Corresponding protective measures need to be taken during use, and they will also have a certain impact on the product quality and performance.

[0030] Compared with organotin catalysts, titanate and its complex catalysts have relatively low catalytic activity, and higher dosages are required to achieve the same catalytic effect.

[0031] Dibutyltin dilaurate has high catalytic activity and can significantly increase the reaction rate at a relatively low concentration. It is suitable for the production of various polyurethane products, such as polyurethane foams, elastomers, and thermoplastic polyurethanes.

[0032] In some other embodiments, in step S5, the polyurethane foam is selected from at least one of rigid foam, spray foam, flexible foam, high resilience foam, semi-rigid foam, integral skin foam, flame retardant foam, antibacterial foam, or water-based foam. In one embodiment of the present invention, the polyurethane foam used is black high resilience polyurethane foam.

[0033] In step S5, the mass-volume ratio of the polyurethane foam to the polyurethane wet gel is (0.78 - 1) g : (21 - 63) mL.

[0034] In some other embodiments, in step S6, the specific steps of the solution replacement are as follows:

[0035] The polyurethane wet gel immersed with the polyurethane foam is repeatedly rinsed with n-hexane solvent. After 10 minutes, the wet gel is immersed in the n-hexane solvent, and the replacement is carried out once every 12 h, repeating 3 times.

[0036] In some other embodiments, in step S6, the conditions for atmospheric drying are: temperature is 40 - 60 °C; drying pressure is 0.1 Mpa; drying time is 24 - 48 h.

[0037] In a second aspect, the present invention provides a polyurethane foam / polyurethane composite aerogel prepared by the preparation method described in the first aspect. The tensile strength of the polyurethane foam / polyurethane composite aerogel is 0.8 - 2.78 Mpa; the shrinkage rate is 7.8 - 11.1%; the porosity is 75 - 85%.

[0038] In a third aspect, the present invention provides the application of the polyurethane foam composite polyurethane aerogel described in the second aspect as a flame retardant material. The oxygen index of the polyurethane foam composite polyurethane aerogel reaches 25% - 29%, and it self-extinguishes when removed from the fire.

[0039] From the above technical solutions, it can be seen that the present invention has achieved the following beneficial effects:

[0040] (1) In the present invention, the polyurethane foam and the polyurethane aerogel are compounded through a semi-interpenetrating network structure. The granular flame retardant polyurethane aerogel is filled into the honeycomb-like polyurethane foam structure as a filler, significantly improving the flame retardant performance of the composite. At the same time, the foam acts as a skeleton, which can further increase the porosity of the composite material and significantly reduce the shrinkage of the polyurethane aerogel.

[0041] (2) The polyurethane foam / polyurethane aerogel composite prepared by the present invention has advantages such as high flame retardancy and high mechanical properties. The oxygen index of the composite reaches 25%-29%, the tensile strength is 0.8-2.78 MPa; the shrinkage rate is 7.8-11.1%; the porosity is 75-85%. Description of the Drawings

[0042] Figure 1 It is an optical picture of the PU foam / PU aerogel of Example 1 of the present invention.

[0043] Figure 2 It is an optical picture of the PU aerogel of Comparative Example 1 of the present invention. The picture shows the appearance characteristics of the polyurethane aerogel, and the surface is relatively rough with irregular textures and shapes.

[0044] Figure 3 It is an SEM image of the PU foam / PU aerogel of Example 1 of the present invention.

[0045] Figure 4 It is an optical picture of the combustion of the PU foam / PU aerogel of Example 1 of the present invention.

[0046] Figure 5 It is an optical picture of the combustion of the PU foam used in the present invention. Detailed Embodiments

[0047] The present invention will be further described in conjunction with specific examples. The following examples are only for explaining the present invention and do not limit its content. If the specific experimental conditions are not specified in the examples, they are usually in accordance with conventional conditions or the conditions recommended by the sales company; in the present invention, without special limitation, the following solvents can be obtained through commercial channels.

[0048] The technical solution of the present invention will be further elaborated below in conjunction with specific embodiments.

[0049] Example 1

[0050] (1) At 25°C, 16 mL of hexamethylene diisocyanate was dissolved in 10 mL of acetonitrile solution, and then stirred for 10 min to obtain a prepolymer solution;

[0051] (2) Dissolve 6 mL of triethylene glycol in 15 mL of acetonitrile solution, then stir for 10 min, then add the mixed solution from step (1), stir for 10 min to form a precursor solution; add 3 mL of TCPP solution to mix with the precursor solution, stir for 10 min to form a mixed solution; dropwise add 0.01 mL of dibutyltin dilaurate to the mixed solution, stir for 20 min. Quickly add three pieces of 0.3 g black high-resilience PU foam, impregnate in a vacuum oven (vacuum degree about 10 Pa, at room temperature) for 5 min, and then put it into a constant temperature drying oven at 25 °C for 2 h to obtain PU foam / PU composite wet gel;

[0052] (3) Immerse the PU foam / PU composite wet gel in step (2) in n-hexane solution for 48 h for aging;

[0053] The specific steps are as follows: repeatedly rinse the PU wet gel impregnated with PU foam with the replacement solvent n-hexane, after 5 - 10 minutes, immerse the wet gel in the replacement solvent, replace it every 12 h, and repeat 4 times.

[0054] (4) Carry out atmospheric pressure drying on the above-aged PU foam / PU composite wet gel to obtain polyurethane foam composite polyurethane aerogel.

[0055] Figure 1 is the optical picture of the prepared polyurethane foam composite polyurethane aerogel. It can be clearly seen from the figure that the polyurethane foam composite polyurethane aerogel has good blockiness. The test results show that the oxygen index of the polyurethane foam composite polyurethane aerogel prepared in Example 1 is 28.4%, it self-extinguishes when removed from the fire, the compressive strength is 2.48 MPa, and the shrinkage rate is 10.8%, indicating that the filling of polyurethane aerogel significantly enhances the mechanical properties of PU foam.

[0056] Figure 3 is the SEM image of the prepared polyurethane foam composite polyurethane aerogel. It can be clearly seen that through the polyurethane foam composite aerogel filled with polyurethane aerogel, a semi-interpenetrating network structure is formed between the polyurethane foam and the polyurethane aerogel, where the granular flame-retardant polyurethane aerogel is filled into the honeycomb-like polyurethane foam structure as a filler; the foam acts as a skeleton, which can significantly reduce the high shrinkage of the polyurethane aerogel, and at the same time improve the porosity and mechanical properties of the composite material; the introduction of polyurethane foam can interrupt the continuous phase of the polyurethane aerogel to form an interfacial thermal resistance, thereby greatly reducing the thermal conductivity of the composite material. In addition, the porous structure of the foam and the nano-pores of the aerogel act synergistically to further increase the porosity of the composite material and significantly reduce the shrinkage of the polyurethane aerogel. At the same time, the porosity is uniform. According to the GB / T21650.1 - 2008 standard, the third-party test result is 83%. Figure 4It is an optical picture of the combustion of the PU foam / PU aerogel in Example 1 of the present invention at 600 °C. The size of the flame after ignition is smaller than that of the PU foam, and it burns more slowly. Moreover, the polyurethane foam composite polyurethane aerogel will self-extinguish after the flame is removed. Figure 5 It is an optical picture of the combustion of the PU foam at 600 °C. After ignition, the flame is very large and burns out quickly, and it will not self-extinguish after the flame is removed.

[0057] Example 2

[0058] (1) At 25 °C, dissolve 17 mL of hexamethylene diisocyanate in 20 mL of acetonitrile solution, and then stir for 10 min to obtain a prepolymer solution;

[0059] (2) Dissolve 6 mL of triethylene glycol in 20 mL of acetonitrile solution, then stir for 10 min, then add the mixed solution in step (1), stir for 10 min to form a precursor solution; add 2.5 mL of TCPP solution to mix with the precursor solution, stir for 10 min to form a mixed solution; dropwise add 0.01 mL of dibutyltin dilaurate to the mixed solution, stir for 20 min. Quickly add three pieces of 0.3 g black high resilience PU foam, immerse it in a vacuum oven for 5 min, and then put it into a constant temperature drying oven at 25 °C for 2 h to obtain a PU foam / PU composite wet gel;

[0060] (3) Immerse the PU foam / PU composite wet gel in step (2) in n-hexane solution for 36 h;

[0061] The specific steps are as follows: repeatedly rinse the PU wet gel immersed with PU foam with n-hexane. After 5 min, immerse the wet gel in the replacement solvent, replace it every 12 h, and repeat 3 times.

[0062] (4) Carry out atmospheric drying on the above-aged PU foam / PU composite wet gel to obtain a polyurethane foam composite polyurethane aerogel.

[0063] The test results show that the oxygen index of the polyurethane foam composite polyurethane aerogel is 27.9%, it self-extinguishes after the flame is removed, the compressive strength is 2.78 MPa, the shrinkage rate is 8.9%, and the porosity is 80%.

[0064] Example 3

[0065] (1) At 25 °C, dissolve 8 mL of hexamethylene diisocyanate in 15 mL of acetonitrile solution, and then stir for 10 min to obtain a prepolymer solution;

[0066] (2) Dissolve 4 mL of triethylene glycol in 20 mL of acetonitrile solution, then stir for 10 min, then add the mixed solution from step (1), stir for 10 min to form a precursor solution; add 1 mL of TCPP solution to mix with the precursor solution, stir for 10 min to form a mixed solution; dropwise add 0.01 mL of dibutyltin dilaurate to the mixed solution, stir for 20 min. Quickly add three pieces of 0.3 g black high-resilience PU foam, impregnate in a vacuum oven for 5 min and then place in a constant temperature drying oven at 25 °C for 2 h to obtain a PU foam / PU composite wet gel;

[0067] (3) Immerse the PU foam / PU composite wet gel from step (2) in n-hexane solution for 48 h;

[0068] The specific steps are as follows: repeatedly rinse the PU wet gel impregnated with PU foam with n-hexane, after 5 - 10 minutes, immerse the wet gel in the displacement solvent, replace it every 12 h, and repeat 4 times.

[0069] (4) Carry out atmospheric drying on the above-aged PU foam / PU composite wet gel to obtain a polyurethane foam composite polyurethane aerogel.

[0070] The test results show that the oxygen index of the polyurethane foam composite polyurethane aerogel is 26.5%, it self-extinguishes after leaving the fire for a while, the compressive strength is 0.8 MPa, the shrinkage rate is 11.1%, and the porosity is 75%.

[0071] Example 4

[0072] (1) Under the condition of 25 °C, dissolve 8 mL of hexamethylene diisocyanate in 10 mL of acetonitrile solution, then stir for 10 min to obtain a prepolymer solution;

[0073] (2) Dissolve 2.67 mL of triethylene glycol in 15 mL of acetonitrile solution, then stir for 10 min, then add the mixed solution from step (1), stir for 10 min to form a precursor solution; add 1 mL of TCPP solution to mix with the precursor solution, stir for 10 min to form a mixed solution; dropwise add 0.01 mL of dibutyltin dilaurate to the mixed solution, stir for 20 min. Quickly add three pieces of 0.3 g black high-resilience PU foam, impregnate in a vacuum oven for 5 min and then place in a constant temperature drying oven at 25 °C for 2 h to obtain a PU foam / PU composite wet gel;

[0074] (3) Immerse the PU foam / PU composite wet gel from step (2) in n-hexane solution for 48 h;

[0075] The specific steps are as follows: repeatedly rinse the PU wet gel impregnated with PU foam with n-hexane, after 5 - 10 minutes, immerse the wet gel in the displacement solvent, replace it every 12 h, and repeat 4 times.

[0076] (4) Subject the above-mentioned aged PU foam / PU composite wet gel to atmospheric pressure drying to obtain a polyurethane foam composite polyurethane aerogel.

[0077] The test results show that the oxygen index of the polyurethane foam composite polyurethane aerogel is 26.2%, it self-extinguishes after leaving the fire for a period of time, the compressive strength is 1.2 MPa, the shrinkage rate is 10.2%, and the porosity is 76%.

[0078] Example 5

[0079] (1) At 25 °C, dissolve 16 mL of hexamethylene diisocyanate in 20 mL of acetonitrile solution, and then stir for 10 min to obtain a prepolymer solution;

[0080] (2) Dissolve 6.23 mL of triethylene glycol in 20 mL of acetonitrile solution, then stir for 10 min, then add the mixed solution from step (1), stir for 10 min to form a precursor solution; add 3 mL of TCPP solution to mix with the precursor solution, stir for 10 min to form a mixed solution; dropwise add 0.02 mL of dibutyltin dilaurate to the mixed solution, stir for 20 min. Quickly add three pieces of 0.3 g black high resilience PU foam, immerse in a vacuum oven for 5 min and then put it into a constant temperature drying oven at 25 °C for 2 h to obtain a PU foam / PU composite wet gel;

[0081] (3) Immerse the PU foam / PU composite wet gel in step (2) in n-hexane solution for 36 h;

[0082] The specific steps are as follows: repeatedly rinse the PU wet gel immersed with PU foam with the replacement solvent n-hexane, after 10 min, immerse the wet gel in the replacement solvent, replace it every 12 h, and repeat 3 times.

[0083] (4) Subject the above-mentioned aged PU foam / PU composite wet gel to atmospheric pressure drying to obtain a polyurethane foam composite polyurethane aerogel.

[0084] The test results show that the oxygen index of the polyurethane foam composite polyurethane aerogel is 28.4%, it self-extinguishes when leaving the fire, the compressive strength is 2.78 MPa, the shrinkage rate is 7.8%, and the porosity is 82%.

[0085] Example 6

[0086] (1) At 25 °C, dissolve 9 mL of hexamethylene diisocyanate in 15 mL of acetonitrile solution, and then stir for 10 min to obtain a prepolymer solution;

[0087] (2) Dissolve 4 mL of triethylene glycol in 15 mL of acetonitrile solution, then stir for 10 min, then add the mixed solution from step (1), stir for 10 min to form a precursor solution; add 2 mL of TCPP solution to mix with the precursor solution, stir for 10 min to form a mixed solution; dropwise add 0.03 mL of dibutyltin dilaurate to the mixed solution, stir for 20 min. Quickly add three pieces of 0.3 g black high-resilience PU foam, immerse in a vacuum oven for 5 min and then put it into a constant temperature drying oven at 25 °C for 2 h to obtain a PU foam / PU composite wet gel;

[0088] (3) Immerse the PU foam / PU composite wet gel in step (2) in n-hexane solution for 48 h;

[0089] The specific steps are as follows: repeatedly rinse the PU wet gel impregnated with PU foam with the replacement solvent n-hexane, immerse the wet gel in the replacement solvent after 5 - 10 minutes, replace it every 12 h, and repeat 4 times.

[0090] (4) Carry out atmospheric drying on the above-aged PU foam / PU composite wet gel to obtain a polyurethane foam composite polyurethane aerogel.

[0091] The test results show that the oxygen index of the polyurethane foam composite polyurethane aerogel is 27.2%, it self-extinguishes after leaving the fire for a while, the compressive strength is 1.5 MPa, the shrinkage rate is 9.9%, and the porosity is 80%.

[0092] Example 7

[0093] (1) Under the condition of 25 °C, dissolve 12 mL of hexamethylene diisocyanate in 20 mL of acetonitrile solution, then stir for 10 min to obtain a prepolymer solution;

[0094] (2) Dissolve 5 mL of triethylene glycol in 20 mL of acetonitrile solution, then stir for 10 min, then add the mixed solution from step (1), stir for 10 min to form a precursor solution; add 0.5 mL of TCPP solution to mix with the precursor solution, stir for 10 min to form a mixed solution; dropwise add 0.01 mL of dibutyltin dilaurate to the mixed solution, stir for 20 min. Quickly add three pieces of 0.4 g black high-resilience PU foam, immerse in a vacuum oven for 5 min and then put it into a constant temperature drying oven at 25 °C for 2 h to obtain a PU foam / PU composite wet gel;

[0095] (3) Immerse the PU foam / PU composite wet gel in step (2) in n-hexane solution for 48 h;

[0096] The specific steps are as follows: repeatedly rinse the PU wet gel immersed in the PU foam with the replacement solvent n-hexane. After 5 - 10 minutes, immerse the wet gel in the replacement solvent, and replace it every 12 h, repeating 4 times.

[0097] (4) Carry out atmospheric drying on the above-mentioned aged PU foam / PU composite wet gel, and then the PU foam / PU composite aerogel can be obtained.

[0098] The test results show that the oxygen index of the PU foam / PU composite aerogel is 25.1%, it self-extinguishes after leaving the fire for a period of time, the compressive strength is 1.79 MPa, the shrinkage rate is 9.5%, and the porosity is 79%.

[0099] The application scenarios targeted by the products of the present invention: It can be used as a fireproof partition material, such as in the stairwells, pipe shafts, etc. of buildings, which can effectively prevent the spread of flames and smoke between different areas and prevent the expansion of fires. As a flame retardant and heat insulation material for electric vehicle battery packs, it can prevent fires caused by overheating or malfunctions of the battery, and prevent the spread of fire to other parts of the battery pack in case of a fire, improving the safety of the battery pack. As a fireproof partition material on ships, such as being set between different cabins, between the engine room and other areas, it can prevent the passage of fire and smoke, improving the fire protection level and safety of the ship.

[0100] Comparative Example 1

[0101] Different from Example 1, polyurethane foam is not added in step (2), and other steps are exactly the same as those in Example 1.

[0102] Polyurethane foam was not added in Comparative Example 1, and the strength was greatly reduced, and the shrinkage rate was greatly reduced. The test results show that the oxygen index of the PU aerogel in Comparative Example 1 is 27%, it self-extinguishes after leaving the fire for a period of time, the compressive strength is 0.5 MPa, the shrinkage rate is 15.3%, and the porosity is 72%. The optical pictures are as Figure 2 shown, and the appearance characteristics of the obtained product are that the surface is relatively rough with irregular textures and shapes.

[0103] Comparative Example 2

[0104] Different from Example 1, polyurethane foam is not added in step (2), and the content of the flame retardant is increased, and other steps are exactly the same as those in Example 1.

[0105] The oxygen index of the PU aerogel in Comparative Example 2 is 28.5%, it self-extinguishes when leaving the fire, the compressive strength is 0.57 MPa, the shrinkage rate is 13.9%, and the porosity is 69.9%.

[0106] The above are only the preferred examples of the present invention and are not intended to limit the present invention. For those skilled in the art, various modifications and changes can be made to the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.

Claims

1. A preparation method of a polyurethane foam composite polyurethane aerogel with high flame retardancy performance, characterized in that, It includes the following steps: S1: Dissolve the isocyanate in an organic solvent, and then stir to obtain a prepolymer solution; S2: Dissolve the polyol in an organic solvent, and then add the prepolymer solution of S1, and stir to form a precursor solution; S3: Mix the flame retardant with the precursor solution prepared in S2 to form a mixed solution; S4: Add a catalyst to the mixed solution prepared in S3 for reaction, and obtain a polyurethane wet gel after crosslinking; S5: Immerse the polyurethane foam fully into the polyurethane wet gel prepared in S4 to obtain polyurethane foam / polyurethane wet gel; S6: Perform solvent replacement on the polyurethane foam / polyurethane wet gel prepared in S5; S7: Perform atmospheric drying on the polyurethane foam / polyurethane wet gel after solvent replacement in S6, and then the polyurethane foam composite polyurethane aerogel is obtained.

2. The preparation method according to claim 1, characterized in that, In step S1, the organic solvent is acetonitrile; The isocyanate is hexamethylene diisocyanate; The volume ratio of the amounts of the organic solvent and the isocyanate used is 1 - 20:8 - 17.

3. The preparation method according to claim 1, characterized in that, In step S2, the polyol is one or more of triethylene glycol, castor oil polyol or polycaprolactone polyol; The organic solvent is acetonitrile; Preferably, the volume ratio of the amounts of the organic solvent and the polyol used is 1 - 20:2.67 - 6.

23.

4. The preparation method according to claim 1, characterized in that, In step S3, the flame retardant is tris(1-chloro-2-propyl) phosphate or ammonium polyphosphate; The volume ratio of the amounts of the precursor and the flame retardant used is 10 - 25:0.5 - 3.

5. The preparation method according to claim 1, wherein In step S4, the volume ratio of the amounts of the precursor and the catalyst used is 10 - 25:0.01 - 0.03; The catalyst is dibutyltin dilaurate.

6. The preparation method according to claim 1, characterized in that, In step S5, the polyurethane foam is selected from at least one of rigid foam, spray foam, soft foam, high resilience foam, semi-rigid foam, self-skinning foam, flame retardant foam, antibacterial foam or waterborne foam.

7. The preparation method according to claim 1, wherein, In step S6, the specific steps of the solution replacement are as follows: Repeatedly rinse the polyurethane wet gel immersed with the polyurethane foam with a replacement solvent. After 5 - 10 minutes, immerse the wet gel in the replacement solvent, and replace it once every 6 - 12 h, and repeat 3 - 5 times.

8. The preparation method according to claim 1, characterized in that, In step S6, the conditions for the atmospheric drying are: the temperature is 40 - 60 °C; the drying pressure is 0.1 Mpa; the drying time is 24 - 48 h.

9. The polyurethane foam composite polyurethane aerogel with high flame retardancy prepared by the preparation method according to any one of claims 1-8, characterized in that The oxygen index of the polyurethane foam composite polyurethane aerogel is 20% - 28.4%, the tensile strength is 0.8 - 2.78 Mpa; the shrinkage rate is 7.8 - 11.1%; the porosity is 75 - 85%.

10. Application of the polyurethane foam composite polyurethane aerogel according to claim 9 as a flame retardant material.

Citation Information

Patent Citations

  • Flame-retardant hydrolysis-resistant polyurethane aerogel and preparation method thereof

    CN114539507A

  • Aerogel composite material as well as preparation method, application and product thereof

    CN115651260A